2013
DOI: 10.1097/scs.0b013e3182801d14
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Sensory Action Potential to Evaluate Inferior Alveolar Nerve Damage After Orthognathic Surgery

Abstract: To assess and monitor the common event of neurosensory disturbance to the inferior alveolar nerve (IAN) after bilateral sagittal split osteotomy, we used clinical sensory tests and neurophysiologic test sensory action potentials. The diagnostic value of these tests was evaluated by comparing them with the degree of nerve damage reported by patients. Fourteen patients undergoing bilateral sagittal split osteotomy were analyzed preoperatively and 2 years postoperatively. Patients were evaluated bilaterally for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 6 publications
0
3
0
1
Order By: Relevance
“…However, previous publications have discussed the variability in the reporting of the percentage of NSD depending on the method of assessment 3 . Patient self-report findings indicate that more than 60% of patients report NSD 6 months after surgery 16 and the alteration can persist for up to 2 years in more than 10% of the patients 1719 . Currently, there is no generally accepted, standard method of assessing sensory disturbances in the distribution of the IAN following mandibular osteotomy or on the sites to be assessed, which makes the comparison of findings from published reports difficult 3,20 .…”
Section: Discussionmentioning
confidence: 99%
“…However, previous publications have discussed the variability in the reporting of the percentage of NSD depending on the method of assessment 3 . Patient self-report findings indicate that more than 60% of patients report NSD 6 months after surgery 16 and the alteration can persist for up to 2 years in more than 10% of the patients 1719 . Currently, there is no generally accepted, standard method of assessing sensory disturbances in the distribution of the IAN following mandibular osteotomy or on the sites to be assessed, which makes the comparison of findings from published reports difficult 3,20 .…”
Section: Discussionmentioning
confidence: 99%
“…All of the above-mentioned tests were carried out in 19 (68%) of the 28 studies included. 6,[12][13][14][15][16]18,[20][21][22][23][24][25][26]29,31,32,35,36 Light touch sensation was measured by Calabria et al 17 light touch and pinprick sensation by Jääskeläinen et al, 27 and de Siquiera et al, 19 and sharp-blunt sensation was reported by Benoliel et al 8 Patients were asked to complete the Ten Test-a selfreported measure of subjective function on the injured side by comparing touch sensation on the injured and uninjured sides and rating sensation on the injured side from 0 to 10 by Mundinger et al 28 Neurosensory function was assessed via questionnaires in 2 studies 7,34 and by patient self-reports only in 1 study. 30 The equipment used to carry out these tests varied among the studies.…”
Section: Diagnostic Tests For Neuropathymentioning
confidence: 99%
“…Three findings of self-reports of patients indicated that >60% of patients reported neurosensory disorders that persisted up to 6 months after surgery, 72 and that the same change could remain for up to 2 years in >10% of patients. 73,74 Therefore, the current findings suggest that the proposed treatment techniques were more efficient in relation to spontaneous improvement.…”
Section: Acupuncture Techniques For Treating Paresthesiamentioning
confidence: 55%